Kurangnya Perhatian Orang Tua Terhadap Pergaulan Bebas Pelajar di Kelurahan Watulambot - Salainti, Yolanda; Pijoh, Feibe Engeline; Mongdong, Novita; Mesra, Romi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Free association that occurs in Watulambot Village needs serious handling because this is very important for the better future of students. deviant behavior that occurs will only bring many bad effects if not handled because there will be more problems that arise from association free among students. The research method used in this study is a qualitative research method. Data collection techniques in this study were carried out by interviews and observation. Data analysis techniques in this study used data analysis techniques from Miles and Hubermen, including data reduction, data display, and conclusion drawing / verification. The results of this study are: the factors that cause promiscuity among students are cultural shifts, lack of attention from parents, and close friends. The impact of promiscuity among students is decreasing school achievement, dropping out of school, and getting pregnant out of wedlock